(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines mental health issues and stress levels among students, focusing on their causes and impact on psychological well-being and academic performance. Factors such as academic pressure, examinations, social environment, and personal challenges are identified as major contributors to increased stress among students. The study also highlights effective psychological strategies and preventive measures aimed at reducing stress and promoting mental well-being. The findings emphasize the importance of supporting students’ mental health within the educational system.